Social Media Marketing and Its Relationship with Customer Loyalty: A Case Study in Cieneguilla, Peru - Olórtegui Alcalde, Luis Miguel (2024)
The objective of this research is to identify the relationship between social media marketing and customer loyalty in a restaurant in Cieneguilla, Peru. The study aims to highlight the importance of leveraging technological innovation to strengthen customer loyalty and improve business competitiveness in the current context. The study fills a gap by exploring how social media marketing affects customer loyalty in a specific sector such as restaurants, an area that has been under-researched in the context of Cieneguilla. Although previous studies have addressed the relationship between social media and loyalty, no comprehensive analysis has been conducted in this geographic and commercial area. The study has a quantitative approach, correlational type, and non-experimental design. A sample of 385 restaurant customers was used, with questionnaires of 22 items for the social media marketing variable and 23 items for the customer loyalty variable. Data collection was processed using the IBM SPSS 27.0 program, and Cronbach's alpha coefficient was used to measure the reliability of the instruments. The results show a low positive correlation between social media marketing and customer loyalty (r = 0.359). It is concluded that as the company improves its social media marketing strategies, the level of customer loyalty increases. However, the implementation of these strategies is still perceived as average by most customers.